The contribution of structural design to green building rating systems: An industry perspective and comparison of life cycle energy considerations. (August 2015) - Miller, Dane; Doh, Jeung-Hwan; Panuwatwanich, Kriengsak; van Oers, Niek
Abstract: The construction industry provides extensive impacts to the environment with population increases further driving these pressures. In an attempt to mitigate these impacts, the industry as a whole has promoted and developed numerous green building rating systems (GBRS). These GBRS assign scores to buildings based on a variety of assessment criteria to determine a structures environmental impact. Previous research has identified shortfalls in certain areas related to these GBRS. In order to gain further insight into these systems an industry survey was conducted to establish an alternate perspective. The outcomes of this survey were consistent with that of previous research, identifying the requirement for an increase in the Embodied Energy (EE) consideration of structures in GBRS. The average estimation of the contribution of EE to a structures life cycle consumption was 28.4%. The survey findings also identified a number of other key areas through which changes in the consideration of sustainable development could be improved. The use of these findings and their comparison to previous research outcomes would assist in the development of supplementary mechanisms to improve the assessment of the environmental performance of structures.